Company law and the protection of creditors' interests: from capital maintenance to solvency and liquidity and beyond - a South African perspective - Arnot, Michael James (University of Cape Town, 2016)
Company law in South Africa has recently been subject to an extensive review which culminated in the passing of a new act, being the Companies Act No. 71 of 2008 (hereinafter 'the new companies Act or 'new Act'). The new Act has not yet come into effect but officials at the Companies and Intellectual Property Office remain optimistic that the new legislation will become effective before the end of the year. The new Act takes South African company law away from its English law roots and brings it into line with international trends. Indeed the South Africanisation of company law was one of the stated objectives of the review process; it being held to be important that the unique characteristics of the South African context and especially the promotion of equity as envisaged under the Constitution be taken into account in the drafting our laws. This research paper is primarily concerned with the legislature's efforts to protect company creditors' interests via mechanisms designed to maintain the economic or capital base of a company. Historically this found expression in the capital maintenance rule but problems with this rule resulted in it being shelved in favour of a regime based on solvency and liquidity. The concept of imposing solvency and liquidity requirements on companies in certain instances was introduced into South African company law in amendments to the existing Companies Acts promulgated in 1999. This resulted in the fragmented approach to the maintenance of an economic or capital base of a company that we currently face: certain areas being subject to the newly imposed solvency and liquidity requirements while at the same time other provisions built around capital maintenance remaining in force.